Systematic Review: The Role of Physical Activity on The Incidence of Dysmenorrhea in Adolescents Aged 12-18 Years - Bratakusumah, Shinta Putri; Aqila, Fayyaza; Wulandari, Chairunnisa Wahid; Alvianty, Rizka Ayu; Nurcandra, Fajaria (Universitas Muhammadiyah Surakarta, 2025)
Pendahuluan: Sebanyak 54,89% remaja di Indonesia mengalami kejadian dismenore jenis primer, sedangkan 45,11% remaja mengalami kejadian dismenore dengan jenis sekunder. Dismenore mempengaruhi terbatasnya aktivitas yang dapat dilakukan oleh remaja putri. Tujuan dari penulisan artikel ini yaitu untuk meninjau seberapa besar pengaruh aktivitas fisik terhadap kejadian dismenore pada remaja. Metode: Dalam proses penelusuran artikel menggunakan beberapa sumber database online seperti Google Scholar, Science Direct, Pubmed, dan Garuda dengan rentang tahun 2014 – 2024. Sistematika penyusunan artikel ini menggunakkan metode tinjauan sistematis dengan pedoman PRISMA (Preferred Reporting Item for Systematic Review and Meta-Analysis), PECO (Population, Exposure, Comparison, Outcome), dan pendekatan cross-sectional untuk mengidentifikasi artikel yang akan digunakan. Hasil: Hasil menunjukkan bahwa dari 7 artikel yang terinklusi terdapat 6 artikel yang mengatakan keterkaitan antara aktivitas fisik dengan dismenore. Simpulan: Dengan demikian, aktivitas fisik memiliki dampak yang signifikan terhadap remaja putri saat mengalami menstruasi. Oleh karena itu, diperlukannya bagi remaja untuk melakukan aktivitas fisik agar terhindar dari kejadian dismenore pada saat menstruasi. Introduction: The prevalence of dysmenorrhea in Indonesia is 54.89% for primary dysmenorrhea while 45.11% for secondary dysmenorrhea. Dysmenorrhea affects the limited activities that can be done by adolescent girls. The justification for writing this article is to find out the impact of physical activity on the prevalence of dysmenorrhea in adolescents. Method: The literature search process contained several online databases such as Google Scholar, ScienceDirect, Pubmed, and Garuda, and it spanned the years 2014 - 2024. The method that was applied when arranging this article is a systematic review method with PRISMA (Preferred Reporting Item for Systematic Review and Meta-Analysis) guidelines. Also, it uses the PECO (Population, Exposure, Comparison, Outcome) method in identifying articles to be used, and the approach used is cross-sectional. Included articles will be selected based on the NOS assessment, so 9 articles have met the criteria. Results: The results stated that of the 9 included articles, 8 articles revealed there was an association between the role of physical activity and the prevalence of dysmenorrhea. Conclusion: It may inferred that physical activity has a significant influence on adolescent girls during menstruation. Therefore, adolescents need to do physical activity to avoid the prevalence of dysmenorrhea during menstruation.